2022
DOI: 10.3390/plants11151898
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics Study of Aux/IAA Family Genes and Their Expression in Response to Different Hormones Treatments during Japanese Apricot Fruit Development and Ripening

Abstract: Auxin/indole-3-acetic acid (Aux/IAA) is a transcriptional repressor in the auxin signaling pathway that plays a role in several plant growth and development as well as fruit and embryo development. However, it is unclear what role they play in Japanese apricot (Prunus mume) fruit development and maturity. To investigate the role of Aux/IAA genes in fruit texture, development, and maturity, we comprehensively identified and expressed 19 PmIAA genes, and demonstrated their conserved domains and homology across s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 67 publications
2
4
0
Order By: Relevance
“…In the present study, a total of 29 Aux/IAA genes were identified in watermelon. Among these, 24 genes exhibited amino acid sequences consisting of less than 500 residues, which aligns with the findings reported in previous studies conducted on Arabidopsis [43], tomato [5], cucumber [6], and Japanese apricot [9] crops. Conversely, only five genes (ClIAA4, 5, 8, 17, and 29) displayed unusually elongated sequences, ranging from 714 to 1491 amino acids.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In the present study, a total of 29 Aux/IAA genes were identified in watermelon. Among these, 24 genes exhibited amino acid sequences consisting of less than 500 residues, which aligns with the findings reported in previous studies conducted on Arabidopsis [43], tomato [5], cucumber [6], and Japanese apricot [9] crops. Conversely, only five genes (ClIAA4, 5, 8, 17, and 29) displayed unusually elongated sequences, ranging from 714 to 1491 amino acids.…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, the up-regulation of FaAux/IAAs transcripts may be partially attributed to auxin-induced fruit growth and the delayed ripening process in strawberry [21]. Additionally, similar key Aux/IAA genes associated with fruit ripening have been identified in Japanese apricot and papaya [7,9]. In a recent study, the utilization of BSA-Seq sequencing in conjunction with transcriptome data analysis unveiled the potential role of an IAA protein (cla004102) and an ethylene response factor (cla004120) as putative regulators of watermelon flesh firmness [22].…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…As a primary auxin-responsive gene family, Aux/IAA genes respond quickly to auxin treatment to regulate downstream genes [ 39 ]. Previous studies have focused on tissue expression patterns and plant development of Aux/IAA genes [ 40 ]. In this study, to understand how the MoIAAs respond to NAA treatment in callus induction and shoot regeneration of M. oleifera , the leaf explants were inoculated with different NAA concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…GmDNJ1 was extensively expressed under ideal growth circumstances and significantly activated in abiotic stress treatments. GmDNJ1 (a type-I HSP40) is important for soybean plant development and heat tolerance, likely due to its role in monitoring misfolded proteins for refolding to maintain the range of cellular activities [ 41 ]. The BIL gene encodes a protein belonging to the mitochondrial Hsp40 family.…”
Section: Discussionmentioning
confidence: 99%